Inovasi Penentuan Pasar Sasaran untuk Meningkatkan Daya Saing Koperasi di Era Globalisasi dan Digitalisasi - Rusmiati, Rusmiati; Mutiarani, Mutiarani; Royani, Novi (Economie: Jurnal Ilmu Ekonomi, 2025)
Cooperatives are one of the many industries that have experienced significant changes due to advances in information technology in the era of the Industrial Revolution 4.0. To become more competitive, cooperatives must innovate, especially when it comes to identifying target markets. To reach new markets and improve operational effectiveness, cooperatives can use digital transformation to develop imaginative and creative characters, implement IT systems, and rebrand. This research uses a literature review method. In this digital era, having a proper cooperative development plan is essential to overcome the increasingly complicated and dynamic competition. Through innovative target market identification, cooperatives can enhance their competitiveness in domestic and international markets by better understanding the needs of members and the market, and developing products and services accordingly.